Odpowiedź :
m₁= 10 kg
m₂= 20 kg
v= 1 m/s
v₂= 0
v₁- ?
m₁v₁ + m₂v₂ = m₁v + m₂v
ponieważ v₂= 0 równanie ma postać
m₁v₁= v(m₁ + m₂)
v₁= (v(m₁ + m₂))/m₁
v₁= (10 + 20) / 10
v₁= 3 m/s
m₂= 20 kg
v= 1 m/s
v₂= 0
v₁- ?
m₁v₁ + m₂v₂ = m₁v + m₂v
ponieważ v₂= 0 równanie ma postać
m₁v₁= v(m₁ + m₂)
v₁= (v(m₁ + m₂))/m₁
v₁= (10 + 20) / 10
v₁= 3 m/s
m₁v₁ + m₂v₂ = m₁v + m₂v
ponieważ v₂= 0 równanie ma postać
m₁v₁= v(m₁ + m₂)
v₁= (v(m₁ + m₂))/m₁
v₁= (10 + 20) / 10
v₁= 3 m/s
ponieważ v₂= 0 równanie ma postać
m₁v₁= v(m₁ + m₂)
v₁= (v(m₁ + m₂))/m₁
v₁= (10 + 20) / 10
v₁= 3 m/s